The Conservative governments and social policy - Bochel, Hugh ca. 20./21. Jh; Powell, Martin 1961- (Policy Press, 2024)
This book examines the policy approaches of Conservative governments since 2015 in key social policy areas including education, health, housing, employment, children and young people and more